Human Endomyocardial Biopsy Specimen-Derived Stromal Cells Modulate Angiotensin II-Induced Cardiac Remodeling. (26th July 2016) - Miteva, Kapka; Van Linthout, Sophie; Pappritz, Kathleen; Müller, Irene; Spillmann, Frank; Haag, Marion; Stachelscheid, Harald; Ringe, Jochen; Sittinger, Michael; Tschöpe, Carsten
Abstract : This study evaluated whether intramyocardial injection of cardiac-derived adherent proliferating cells (CardAPs) modulates cardiac fibrosis and hypertrophy in a mouse model of angiotensin II (Ang II)-induced systolic heart failure and analyzed underlying mechanisms. Among other findings, results indicated that intramyocardial injection of CardAPs improved left ventricular (LV) function and reduced LV remodeling. These improvements were attributed to antifibrotic and antihypertrophic effects resulting from paracrine actions and immunomodulatory properties. Abstract : Cardiac-derived adherent proliferating cells (CardAPs) are cells derived from human endomyocardial biopsy specimens; they share several properties with mesenchymal stromal cells. The aims of this study were to evaluate whether intramyocardial injection of CardAPs modulates cardiac fibrosis and hypertrophy in a mouse model of angiotensin II (Ang II)-induced systolic heart failure and to analyze underlying mechanisms. Intramyocardial application of 200, 000 CardAPs improved left ventricular function. This was paralleled by a decline in left ventricular remodeling, as indicated by a reduction in cardiac fibrosis and hypertrophy. CardAPs reduced the ratio of the left ventricle to body weight and cardiac myosin expression (heavy chain), and decreased the Ang II-induced phosphorylation state of the cardiomyocyte hypertrophy mediators Akt, extracellular-signal regulated kinase (ERK) 1, and ERK2. In accordance with the antifibrotic and antihypertrophic effects of CardAPs shown in vivo, CardAP supplementation with cardiac fibroblasts decreased the Ang II-induced reactive oxygen species production, α-SMA expression, fibroblast proliferation, and collagen production. Coculture of CardAPs with HL-1 cardiomyocytes downregulated the Ang II-induced expression of myosin in HL-1. All antifibrotic and antihypertrophic features of CardAPs were mediated in a nitric oxide- and interleukin (IL)-10-dependent manner. Moreover, CardAPs induced a systemic immunomodulation, as indicated by a decrease in the activity of splenic mononuclear cells and an increase in splenic CD4CD25FoxP3, CD4-IL-10, and CD8-IL-10 T-regulatory cells in Ang II mice. Concomitantly, splenocytes from Ang II CardAPs mice induced less collagen in fibroblasts compared with splenocytes from Ang II mice. We conclude that CardAPs improve Ang II-induced cardiac remodeling involving antifibrotic and antihypertrophic effects via paracrine actions and immunomodulatory properties. Significance : Despite effective pharmacological treatment with angiotensin II type I receptor antagonists or angiotensin II-converting enzyme inhibitors, morbidity and mortality associated with heart failure are still substantial, prompting the search of novel therapeutic strategies. There is accumulating evidence supporting the use of cell therapy for cardiac repair. This study demonstrates that cells derived from human endomyocardial biopsies, cardiac-derived adherent proliferating cells (CardAPs), have the potential to reduce angiotensin II-induced cardiac remodeling and improve left ventricular function in angiotensin II mice. The mechanism involves antifibrotic and antihypertrophic effects via paracrine actions and immunomodulatory properties. These findings support the potential of CardAPs for the treatment of heart failure.